Spatial-to-spectral phase coupling mechanisms in bulk continuum generation - Benjamin Maingot; Nicolas Forget; Aurélie Jullien (JPhys Photonics)
We study the coherence properties of continuum generation in YAG crystals seeded by 180 fs pulses at 1035 nm when the driving beam exhibits small fluctuations of the spatial phase. The relative stability of the continuum spectral phase is first assessed as a function of the driver wavefront aberrations. Furthermore, we evidence and quantify a coupling mechanism between these fluctuations and the spectral phase of the continuum. The coupling coefficients increase with the spectral broadening and are also unexpectedly large (up to tens of rad/rad at $\simeq$ 750 nm). Experimental evidence supports that longitudinal shifts of the position of the filament within the crystal are responsible for such strong effects.